Effect of the CO2/SiH4 Ratio in the p-μc-SiO:H Emitter Layer on the Performance of Crystalline Silicon Heterojunction Solar Cells - Jaran Sritharathikhun; Taweewat Krajangsang; Apichan Moollakorn; Sorapong Inthisang; Amornrat Limmanee; Aswin Hongsingtong; Nattaphong Boriraksantikul; Tianchai Taratiwat; Nirod Akarapanjavit; Kobsak Sriprapha (International Journal of Photoenergy)
This paper reports the preparation of wide gap p-type hydrogenated microcrystalline silicon oxide (p-μc-SiO:H) films using a 40 MHz very high frequency plasma enhanced chemical vapor deposition technique. The reported work focused on the effects of the CO2/SiH4 ratio on the properties of p-μc-SiO:H films and the effectiveness of the films as an emitter layer of crystalline silicon heterojunction (c-Si-HJ) solar cells. A p-μc-SiO:H film with a wide optical band gap (E04), 2.1 eV, can be obtained by increasing the CO2/SiH4 ratio; however, the tradeoff between E04 and dark conductivity must be considered. The CO2/SiH4 ratio of the p-μc-SiO:H emitter layer also significantly affects the performance of the solar cells. Compared to the cell using p-μc-Si:H (CO2/SiH4 = 0), the cell with the p-μc-SiO:H emitter layer performs more efficiently. We have achieved the highest efficiency of 18.3% with an open-circuit voltage (Voc) of 692 mV from the cell using the p-μc-SiO:H layer. The enhancement in the Voc and the efficiency of the solar cells verified the potential of the p-μc-SiO:H films for use as the emitter layer in c-Si-HJ solar cells.